Specifications of the ACMG/AMP standards and guidelines for mitochondrial DNA variant interpretation. Issue 12 (10th November 2020) - McCormick, Elizabeth M.; Lott, Marie T.; Dulik, Matthew C.; Shen, Lishuang; Attimonelli, Marcella; Vitale, Ornella; Karaa, Amel; Bai, Renkui; Pineda‐Alvarez, Daniel E.; Singh, Larry N.; Stanley, Christine M.; Wong, Stacey; et al.
Abstract: Mitochondrial DNA (mtDNA) variant pathogenicity interpretation has special considerations given unique features of the mtDNA genome, including maternal inheritance, variant heteroplasmy, threshold effect, absence of splicing, and contextual effects of haplogroups. Currently, there are insufficient standardized criteria for mtDNA variant assessment, which leads to inconsistencies in clinical variant pathogenicity reporting. An international working group of mtDNA experts was assembled within the Mitochondrial Disease Sequence Data Resource Consortium and obtained Expert Panel status from ClinGen. This group reviewed the 2015 American College of Medical Genetics and Association of Molecular Pathology standards and guidelines that are widely used for clinical interpretation of DNA sequence variants and provided further specifications for additional and specific guidance related to mtDNA variant classification. These Expert Panel consensus specifications allow for consistent consideration of the unique aspects of the mtDNA genome that directly influence variant assessment, including addressing mtDNA genome composition and structure, haplogroups and phylogeny, maternal inheritance, heteroplasmy, and functional analyses unique to mtDNA, as well as specifications for utilization of mtDNA genomic databases and computational algorithms. Abstract :